188k views
3 votes
Simplify -6(6+10+6v)

User Bonidjukic
by
5.3k points

2 Answers

3 votes

Answer is -96-36v

Work Shown:

The "6+10" in the parenthesis combines to 16. So we really have -6(16+6v)

Use the distribution rule. Multiply the outer -6 by each term inside

-6 times 16 = -96

-6 times 6v = -36v

Put together, we have -6(16+6v) = -96-36v

User Stefano Radaelli
by
5.0k points
4 votes

Answer:

-96 - 36v

Explanation:

You distribute (multiply) the -6 to everything in the parentheses.

-6 * 6 = -36 -6 * 10 = -60 -6 * 6v = -36v

-36 - 60 - 36v

Then combine like terms.

-36 - 60 = -96

Answer:

-96 - 36v

User Ditoslav
by
6.0k points